Acceptability and Feasibility of Portable Eye-Tracking Technology within a Children's Dynamic Sport Context: An Exploratory Study with Boys Who Play Grassroots Football - Katie Fitton Davies; Theresa Heering; Matt Watts; Michael J. Duncan (MDPI AG, 2024)
Teaching practices are moving from decontextualised to more representative curricula. Although this is argued to be a positive step, low motor competence is a continual issue in primary-aged school children. One methodological approach to investigate ways to improve motor competence, eye tracking, is moving to more representative tasks. So far, eye-tracking research using static activities has demonstrated a positive association between motor competence and earlier fixation and longer duration. However, this research has been constrained to laboratory settings and tasks, or discrete activities (e.g., throw and catch). This study seeks to understand how to conduct more representative eye-tracking research in primary school-aged children. To this end, thirteen 10-11-year-old children were fitted with an eye-tracker during a typical football coaching session. Children were asked acceptability-based questions, and eye-gaze data were captured to illustrate what children attended to under a representative dynamic football-based activity. Based on the voices of children and captured eye-gaze data, six practical implications for research in this population are proposed: (1) conduct eye-tracking research indoors (where possible); (2) ensure long hair or fringes are secured so as not to obscure line of sight; (3) run the same activity to increase comparability across children wearing the eye-tracker; (4) use a properly fitted backpack (if a backpack is to be used); (5) assure children about the capability and hardiness of the eye-tracker, as they do not need to change the way they move; (6) explain there may be some discomfort with the nose clip, head strap, and battery weight and ensure that children wish to continue.